Improved Optics in Monolithic Perovskite/Silicon Tandem Solar Cells with a Nanocrystalline Silicon Recombination Junction. Issue 6 (9th October 2017) - Sahli, Florent; Kamino, Brett A.; Werner, Jérémie; Bräuninger, Matthias; Paviet‐Salomon, Bertrand; Barraud, Loris; Monnard, Raphaël; Seif, Johannes Peter; Tomasi, Andrea; Jeangros, Quentin; Hessler‐Wyser, Aïcha; De Wolf, Stefaan; et al.
Abstract: Perovskite/silicon tandem solar cells are increasingly recognized as promising candidates for next‐generation photovoltaics with performance beyond the single‐junction limit at potentially low production costs. Current designs for monolithic tandems rely on transparent conductive oxides as an intermediate recombination layer, which lead to optical losses and reduced shunt resistance. An improved recombination junction based on nanocrystalline silicon layers to mitigate these losses is demonstrated. When employed in monolithic perovskite/silicon heterojunction tandem cells with a planar front side, this junction is found to increase the bottom cell photocurrent by more than 1 mA cm −2 . In combination with a cesium‐based perovskite top cell, this leads to tandem cell power‐conversion efficiencies of up to 22.7% obtained from J – V measurements and steady‐state efficiencies of up to 22.0% during maximum power point tracking. Thanks to its low lateral conductivity, the nanocrystalline silicon recombination junction enables upscaling of monolithic perovskite/silicon heterojunction tandem cells, resulting in a 12.96 cm 2 monolithic tandem cell with a steady‐state efficiency of 18%. Abstract : A nanocrystalline silicon recombination junction is presented, which mitigates reflection losses in monolithic perovskite/silicon heterojunction tandem solar cells, resulting in efficiencies of up to 22.7% on an aperture area of 0.25 cm 2 . Thanks to its low lateral conductance, this recombination junction enables tandem cell up‐scaling, leading to a steady‐state efficiency of 18% on an aperture area of 12.96 cm 2 .